Journal Economics, business & accountancy:MODEL OF INFORMATION SYSTEM OPERATION BASED ON TECHNOLOGY ACCEPTANCE MODEL FOR MICRO FINANCIAL INSTITUTIONS - Atika Jauharia Hatta (PPPM Perbanas, 2011)
Credit union (CU) is an important financial institution for poor society and micro industriesin supporting the fact in which in credit unions, client doesnt require complicated clauseslike other micro finance companies. Yet, traditional ways in accounting system make limitationfor this institution efficient and effective in their operation. By applying an informationsystem, they can increase performance through repairing in planning and managing businessand easier in transaction activity.